Striving for Urban Space: A Case of Street Vendors of Pokhara, Nepal - Khawas, Namrata (Dhaulagiri Journal of Sociology and Anthropology, 2022)
Street vending is an important component of the informal economy of a city. It forms the major base of livelihood for a significant proportion of the urban poor. Embedded with the conceptual, theoretical, and methodological realm of urban anthropology and the right to the city, this article assesses vendors’ striving for subsistence livelihoods amidst the increased rigidness of local authorities towards them in Pokhara. Based on qualitative data collected through the ethnographic fieldwork carried out in the market centers of Pokhara Metropolitan City, this article documents the struggle of women street vendors against challenges posed by metropolis authority and their police, customers, and shopkeepers. As captured in stories, they strive against these challenges to support their livelihood. Their ceaseless striving for urban space for undertaking vending practices continues. The tireless engagement of the street vendors in coping with the adversities created by different agencies is an indication that they have been claiming certain kinds of rights over urban space in Pokhara City.